Global Contemporary Art in the Philippines: A Vantage Point - del Mundo-Angeles, Ana Neliza (Future Science / FSH-PH Publications, 2022)
Philippine art scene had never been more prolific than today. This study aims to be a groundwork for more studies about global contemporary art in the Philippines and how it can help shape the future curriculum of Fine Arts in the country. This study looked into the characteristics of global contemporary art in the Philippines through the professional artists’ and art students’ perspectives using qualitative research method. The research believes that global contemporary art promotes “unity in diversity” to unite nations as one big community sans nationality, color, race, or language. Once the phases of this study is complete, these will be significant to artists and art students who want to be guided on creating contemporary art that can compete globally, as well as academes to have a handy reference for creating global contemporary subjects following an outcomes based curriculum.